PERAMALAN SEPSIS AKIBAT PROCALCITONIN TERKAIT KELUARAN HASIL KLINIS - Umi S. Intansari; Nunung Dartini; Kismardhani Kismardhani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Sepsis is a systemic inflammatory response due to a severe infection. The systemic immune response rises after the local immuneresponse does not successfully eliminate the antigen. Procalcitonin (PCT) has been known as the marker for bacterial infection. The aimof this study was to know whether PCT could be used as a predictor of clinical outcome in sepsis incidence. A prospective cohort designwas used in this study. The subjects were patients entering the Internal ward who met the inclusion and exclusion criteria and examinedfor the basic data collection. For the assessment of SOFA (Sepsis-related Organ Failure Assessment) score, blood specimens were takenfor PCT examination, on the first day since the diagnosis of sepsis and on the third day. The patients were observed until the tenth dayto determine the assessment of their survival analysis. This study involved 50 subjects who fulfilled the inclusion and exclusion criteria.The mean levels of PCT on day I and III were 5.19±5.83 ng/mL and 6.37±9.85 ng/mL, respectively. The mean levels of PCT on day I andIII in the group with increased SOFA score was 5.01±1.17 ng/mL and 3.86±1.46 ng/mL, respectively. The mean levels of PCT on day Iand III in the group without increased SOFA was 5.32±1.21 ng/mL and 4.88±2.21 ng/mL, respectively. The relative risk of increasedPCT against the poor output expressed by the increased SOFA score was 5.75. In the survival analysis, it was shown that 52% of patientssurvived at day 10. In the group of non survival patients; the number of patients with increased PCT was more than that without increasedPCT. Based on this study, it can be concluded that procalcitonin could be used as a predictor for the clinical outcome in sepsis patients.